Получение и исследование восстановительных покрытий на деталях машин с использованием механокомпозитов, содержащих TiC и TiB₂ - Лузан, Сергей Алексеевич; Сидашенко, Александр Иванович; Лузан, Алиса Сергеевна (Приватне підприємство "Ексклюзив-Систем", 2017)
В статье описано исследование восстановительных износостойких покрытий для деталей сельскохозяйственных машин с использованием композиционных материалов, представляющих собой смесь матричного материала и механокомпозита, полученного с применением СВС-процесса. В результате разработан композиционный материал на основе самофлюсующегося сплава системы Ni-Cr-B-Si, модифицированный механокомпозитом, содержащим карбид и диборид титана.

The article describes the study of restorative wear-resistant coatings for agricultural parts using composite materials, which are a mixture of matrix material and mechanocomposite obtained using the SHS process. As a result, a composite material based on a self-fluxing Ni-Cr-B-Si alloy modified with a mechanocomposite containing carbide and titanium diboride was developed. The microstructure of surfaced coatings is the matrix material, which is the granulated powder 10 grinded cladding powder 01 alloy, in which solid inclusions are uniformly distributed, presumably, these are titanium diboride (TiB₂), iron carbide (Fe₃C) particles.
Receiving and researching reparative coatings on machine parts using mechanocomposites containing TiC and TiB₂
Keywords: СВС-процесс; композиционные материалы; механоактивация; матричные материалы; химические элементы; наплавка; износостойкость; SHS-process